An enhanced honey bee mating optimization algorithm for design of side sway steel frames. (July 2017) - Maheri, Mahmoud R; Shokrian, H.; Narimani, M.M.
Highlights: A new enhanced honey bee mating optimization (EHBMO) algorithm is proposed. The algorithm gives added credence to distant candidates which are slightly less feasible than the local candidates. Four benchmark side sway frame design optimization problems are solved. EHBMO is very competitive with other state-of-the-art meta-heuristic optimization algorithms. Abstract: Honeybee mating is a swarm-based meta-heuristic optimization method where the search algorithm is inspired by the process of mating in honeybees. In this paper, a new improved algorithm is proposed which performs remarkably better than the basic honeybee mating optimization process and is very competitive with other meta-heuristic optimization algorithms reported in the literature. The new algorithm, termed as enhanced honey bee mating optimization (EHBMO) algorithm, uses the concept of giving weight to distant candidates which are slightly less feasible than the current local candidates but may hold information about the location of global optima further afield. The robustness of the algorithm in terms of both solution quality and computational cost is proven by solving four design optimization problems of side sway steel frames.